Robust design of digital circuits on foil - Myny, Kris, 1980-; Genoe, Jan, 1965-; Dehaene, Wim (Cambridge University Press, 2016)
A practical guide to the theory and applications of TFT technologies and circuit designs for those in academia and in industry.